Proposed new interior design scheme of Peugeot 3S centre for Nasim Sdn Bhd at Lot 9575 S, Jalan Gopeng, daerah Kinta, bandar Ipoh, Perak / Suhadi Ahmad - AHMAD, SUHADI (2010)
This report is a compulsory subject for student to get Interior Design Diploma at Universiti Teknologi MARA. This subject is a comprehensive exercise about the art of interior design, where student are required to prepare a comprehensive design scheme based on research and observation which is sensitive enough about the issues and problems in interior design. This is a report about a proposal to create new interior design scheme of Peugeot 3S centre for Nasim Sdn Bhd at Lot 9575 S, Jalan Gopeng, Daerah Kinta, Bandar Ipoh Perak. Nasim Sdn Bhd, the distributor of Peugeot vehicles in Malaysia, will undertake a re-branding exercise at all its branches and dealers following the French carmaker's recent unveiling of a new global brand identity. Therefore, the proposal is to create a new interior design scheme equivalent to the new introduced global brand identity. I proposed lot 9575 S, Jalan Gopeng, Daerah Kinta, bandar Ipoh Perak as the site to fulfill the clients request plus the location is located strategically . As in this project, a design of a commercial space and all the aspect related are important and a further study must be conduct to implement a good design inside the space. The design process consists of concept, image, planning and material & finishes. The concept chosen for this showroom is "Motion" which refers to the constant movement/progress of Peugeot toward improving its achievement. The image that will be applied on the design is Deconstrucnism - a function follow form style. Using elements such as wide open spaces, space frames, glass wall, architecture cladding , clean edges and etc, Peugeot 3s Centre at Ipoh will be one of the project people will be looking forward to.